Extraction, isolation and identification of an enzymatic browning product from fresh white salted noodles. (November 2021) - Wang, Yuan-Hui; Li, Hao-Qi; Zhang, Qi-Dong; Zhang, Qiong-Qiong; Zhang, Qiu-Mei; Wang, Xi
Abstract: An enzymatic browning product (EBP) of fresh white salted noodles (FWSNs) was extracted, purified, isolated and identified. The optimum parameters of extraction were as follows: volume fraction of ethanol 70%, solid-liquid ratio 1 : 10 (g: mL, samples: ethanol solution), extraction time 10 days (20 °C). In the purified process, protein (99.86%) and carbohydrates (69.50%) impurities were removed from the crude extract using Sevag method, dialysis method and AB-8 macroporous resin column. The purified EBP was separated using 20% (v: v) methanol solution in a C18 chromatographic column. A monomer of EBP was isolated by high-performance liquid chromatography. Nuclear magnetic resonance and infrared spectroscopy analysis showed that the EBP monomer was 2-hydroxyindole-3-propylamine. This was the first time in the literature that 2-hydroxyindole-3-propylamine was found in the EBP of FWSNs. It would lay a material foundation for investigating the origin of EBPs and the revealing enzymatic browning mechanism of FWSNs. Graphical abstract: Image 1 Highlights: Enzymatic browning product of fresh white salted noodles was extracted 70% ethanol solution at 20 °C. Protein impurity was removed using Sevag method and dialysis method. AB-8 macroporous resin column was used to remove carbohydrate impurity. Enzymatic browning product was preliminarily separated using C18 chromatographic column. An enzymatic browning product isolated by HPLC was 2-hydroxyindole-3-propylamine.